Record of Carnivorous Plant Drosera burmannii Vahl (Caryophyllales: Droseraceae) from Palamau Tiger Reserve, Jharkhand, India - Bakshi, M. K.; Sajan, S. K.; Xaxa, S.; Srivastava, D. S.; Mishra, A. K.; Kazmi, Seh (Indian Forester, 2017)
No Abstract.